2020
DOI: 10.1039/c9dt04332b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structures of mono- and di-nuclear aluminium and zinc complexes bearing α-diimine and related ligands, and their use in the ring opening polymerization of cyclic esters

Abstract: Multi-metallic complexes (of Al, Zn) derived from imine-based ligands effectively operate as catalysts for the ring opening polymerization (ROP) of ε-caprolactone (ε-CL), δ-valerolactone (δ-VL) and co-polymerization thereof.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 78 publications
1
12
0
Order By: Relevance
“…26,27 Among these, multinuclear catalysts showed the most interesting results. 28,29 Because of cooperative effects between reactive centers, 30−34 unexpected activities 31−33,35−38 and selectivity 35 have been often observed. 39−43 In a previous work we reported that dinuclear salen aluminum complexes are efficient catalysts for the polymerization of cyclic esters and the copolymerization of epoxides and anhydrides.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 Among these, multinuclear catalysts showed the most interesting results. 28,29 Because of cooperative effects between reactive centers, 30−34 unexpected activities 31−33,35−38 and selectivity 35 have been often observed. 39−43 In a previous work we reported that dinuclear salen aluminum complexes are efficient catalysts for the polymerization of cyclic esters and the copolymerization of epoxides and anhydrides.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among these, multinuclear catalysts showed the most interesting results. , Because of cooperative effects between reactive centers, unexpected activities , and selectivity have been often observed. …”
Section: Introductionmentioning
confidence: 99%
“…[9] Research on bidentate nitrogen ligand five-membered ring dialkyl aluminum complexes has been widely reported in recent years. For example, α-diimine and 8-Anilide-5,6,7-trihydroquinoline dialkyl aluminum complexes are used as highly active catalysts in the ring-opening polymerization cyclic esters; [12,19] α-diimine and 2-imino pyridine dialkyl aluminum are used to study redox ligands. [10] The properties of planar five-membered ring dialkyl aluminum complexes are valuable to study.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, 1,2-diamines have widespread applications as core structures in a variety of natural products, pharmaceuticals, and agrochemicals [34][35][36][37][38] and are valuable ligands [39,40] in stereoselective organic synthesis. Despite the availability of a plethora of synthetic methods for 1,2-diamines [41][42][43][44][45], the reported photocatalytic synthetic methods are mainly limited to aniline-based substrates and do not encompass aliphatic amines. We planned the synthesis of 1,2-diamine compounds having an aliphatic amine moiety by the intermolecular coupling of N-benzylidines with aliphatic amines that not only act as coupling partner but also as electron donors in the photoredox cycle, and the results are reported herein.…”
Section: Introductionmentioning
confidence: 99%